Can Competitive Athletes Sustain High-Level Play Following Osteochondral Allograft Transplantation of the Knee?. Issue 7 (21st July 2017) - McCarthy, Mark A.; Meyer, Maximilian A.; Weber, Alexander E.; Levy, David; Tilton, Annemarie K.; Yanke, Adam Blair; Cole, Brian J.
Objectives: The purpose of this study is to investigate the ability of competitive athletes to remain at a high level of competition following osteochondral allograft transplantation (OCA) of the knee. Methods: A retrospective review was performed to identify all competitive athletes (high school, collegiate, professional) who underwent an isolated femoral condyle OCA between 2004 and 2012. Patient reported outcome (PRO) questionnaires (Lysholm, International Knee Documentation Committee (IKDC), Knee Injury and Osteoarthritis Outcome Score (KOOS), Western Ontario and McMasters Universities Arthritis Index (WOMAC), Short Form-12 (SF-12), Tegner, and Marx) and custom return-to-sport surveys were administered. All subsequent reoperations were documented. Results: A total of 13 (7 male, 6 female) athletes were identified with an average follow-up of 5.9 ± 2.5 years. Four athletes competed at an intercollegiate level, while 9 played high-level high-school sports. Seven athletes returned to competitive sport (54%) at an average of 7.9 ± 3.5 months, five of whom were returned to pre-injury levels of play. Of the eight athletes who either did not return to sport or failed to sustain their high level of play, the most common reasons cited were a change in life circumstances, such as graduation, or a fear of re-injury (Figure 1). At final follow-up, regardless of return-to-play, all athletes had significant improvements in all PRO scores except for KOOS-Sport, WOMAC-Stiffness, and SF-12 Mental subscales. Tegner Activity scores dropped significantly from pre-injury to final follow-up (8.2 ± 2.4, 4.5 ± 2.1, p < 0.01). There were three reoperations and zero instances of graft failure. Conclusion: OCAs provide acceptable rates of return-to-play and excellent long-term outcomes for high-level athletes with large osteochondral defects. Social factors are three times more likely than persistent pain to prevent return to sport.